Political Conspiracies in America : A Reader - Sherman, Matthew C.; Korasick, John; Critchlow, Donald T., 1948- (Book collections on Project MUSE., 2008)
This anthology provides students with documents relating to some of the more important and interesting conspiracy theories in American history and politics, some based on reality, many chiefly on paranoia. --from publisher description.